APPLICATION OF THE INTEREST SYSTEM IN CONVENTIONAL BANKS AND ITS RELATION TO ISLAMIC LAW REGARDING USURY - M. Husni Ingratubun (Awang Long Law Review, 2022)
Conventional banking operations benefit mainly from the difference between the deposit interest given to customers and the interest or credit loans given. In contrast, in Islamic Banks, the profits they get are not from interest but through profit sharing. The main difference between conventional banks and Islamic banking is the prohibition of Riba (interest) in Islamic banking. Under Sharia banking, bank interest is prohibited while trading is permitted by Allah. Riba is defined as Ziyadah (additional cost). Riba is an additional fee, both in trade transactions and loans that are illegal or contrary to the principles of Muamalah in Islam.